Titanium Complexes with Functional Alkoxido Ligands for Selective Ethylene Dimerization – A High Throughput Experimentation Approach. Issue 9 (25th February 2021) - Grasset, Fabien L.; Welter, Richard; Braunstein, Pierre; Olivier‐Bourbigou, Hélène; Magna, Lionel
Abstract: New titanium complexes of general formula [Ti(OR)2 (O i Pr)2 ], containing functionalized alkoxido ligands, were developed for the selective catalytic dimerization of ethylene to 1‐butene using a combined High Throughput Screening (HTS) / Design of Experiment (DoE) approach. First, a library of 19 ligands was elaborated and a primary screening spotted the phosphorus‐functionalized alkoxido ligands as most promising. A second, more focused library containing 8 alkoxidophosphane ligands was then developed. A longer linear spacer between the alkoxido and the phosphorus functions, as in [Ti(19 )2 (O i Pr)2 ], was found beneficial for this catalytic reaction. After identification of the best co‐catalyst (AlEt3 ) and co‐ligand (O n Bu), final optimization of the reaction conditions was performed using a design of experiments (DoE) approach. The complex [Ti(19 )2 (O n Bu)2 ] was shown to selectively dimerize ethylene in 1‐butene (C4 (α)=93 % (99 + %)) at 30 bar C2 H4 and 55 °C with AlEt3 as co‐catalyst, resulting in very high activity and selectivity for a molecular titanium catalyst (13000 g gTi −1  h −1, 93 % 1‐butene). Abstract : Winning Ti! A combined High Throughput Screening (HTS) / Design of Experiment (DoE) approach, applied to functionalized alkoxido titanium complexes [Ti(OR)2 (O i Pr)2 ], allowed to identify a very active and selective Ti‐based catalyst for ethylene dimerization (13000 g gTi −1  h −1, 93 % 1‐butene) (30 bar C2 H4, 55 °C, co‐catalyst AlEt3 ).